Genomic analysis reveals the biotechnological and industrial potential of levan producing halophilic extremophile, Halomonas smyrnensis AAD6T - TOKSOY ÖNER, EBRU; ARĞA, KAZIM YALÇIN (SPRINGER INTERNATIONAL PUBLISHING AG, 2015)
Halomonas smyrnensis AAD6T is a gram negative, aerobic, and moderately halophilic bacterium, and is known to produce high levels of levan with many potential uses in foods, feeds, cosmetics, pharmaceutical and chemical industries due to its outstanding properties. Here, the whole-genome analysis was performed to gain more insight about the biological mechanisms, and the whole-genome organization of the bacterium. Industrially crucial genes, including the levansucrase, were detected and the genome-scale metabolic model of H. smyrnensis AAD6T was reconstructed. The bacterium was found to have many potential applications in biotechnology not only being a levan producer, but also because of its capacity to produce Pel exopolysaccharide, polyhydroxyalkanoates, and osmoprotectants. The genomic information presented here will not only provide additional information to enhance our understanding of the genetic and metabolic network of halophilic bacteria, but also accelerate the research on systematical design of engineering strategies for biotechnology applications.
Keywords: Halomonas smyrnensis; Halophiles; Genome; Next-generation sequencing; Levan; GLYCINE BETAINE; BINDING-PROTEIN; BACTERIUM; SEQUENCE; EXOPOLYSACCHARIDE; FILMS